2020
DOI: 10.1158/1078-0432.ccr-20-1781
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation in Pomalidomide, Dexamethasone, and Daratumumab-Treated Patients with Relapsed/Refractory Multiple Myeloma

Abstract: Purpose: Addition of daratumumab to pomalidomide and lowdose dexamethasone (LoDEX) is a safe and effective combination for relapsed/refractory multiple myeloma treatment. We sought to better understand immune combinational benefit of pomalidomide and daratumumab with LoDEX. Experimental Design: Immunophenotypic changes were analyzed in peripheral blood from longitudinal sampling of patients treated with this triplet regimen from cohort B of the CC4047-MM-014 phase II trial (NCT01946477). Results: Consistent wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…In the patients that we studied extensively so far, absence of the CD19+ B cell compartment in the peripheral blood was associated with lack of antigen-specific B and also T cell responses. B cell depletion after anti-CD38 monoclonal antibody treatment regimens has been reported [18][19][20] , but the effects of BCMA-targeted treatment modalities on B cell populations (and the general immune composition) is less clear. B cell counts could be measured relatively easily and immunophenotyping in a larger cohort is warranted for independent confirmation of our findings.…”
Section: Discussion (Word Count: 657)mentioning
confidence: 99%
“…In the patients that we studied extensively so far, absence of the CD19+ B cell compartment in the peripheral blood was associated with lack of antigen-specific B and also T cell responses. B cell depletion after anti-CD38 monoclonal antibody treatment regimens has been reported [18][19][20] , but the effects of BCMA-targeted treatment modalities on B cell populations (and the general immune composition) is less clear. B cell counts could be measured relatively easily and immunophenotyping in a larger cohort is warranted for independent confirmation of our findings.…”
Section: Discussion (Word Count: 657)mentioning
confidence: 99%
“…Immunomodulatory data from patients treated with IMiD therapies showed an increase in bone marrow T lymphocytes [ 31 , 32 ]. More recently, modulation of innate and adaptive immunity by POM-based regimens has become more defined and correlated with clinical antitumor effects [ 33 , 34 ]. Notably, POM plus dexamethasone (POMdex), POMdex with cyclophosphamide [ 35 ], or POMdex with DARA [ 33 ] consistently showed decrease in naïve T cells with concurrent increase in effector memory and activated/proliferating T cells.…”
Section: Learnings From the Bedsidementioning
confidence: 99%
“…More recently, modulation of innate and adaptive immunity by POM-based regimens has become more defined and correlated with clinical antitumor effects [ 33 , 34 ]. Notably, POM plus dexamethasone (POMdex), POMdex with cyclophosphamide [ 35 ], or POMdex with DARA [ 33 ] consistently showed decrease in naïve T cells with concurrent increase in effector memory and activated/proliferating T cells. Notably, this enrichment of a differentiated and cytotoxic T cell phenotype by POM-based regimen still occurs in patients refractory to LEN [ 33 ].…”
Section: Learnings From the Bedsidementioning
confidence: 99%
See 1 more Smart Citation
“…Although there are effective therapeutic combinations, patients with MM often relapse and become refractory to standard-of-care treatments such as immunomodulatory imide (IMiD) agents, proteasome inhibitors, and anti-CD38 monoclonal antibodies (e.g., daratumumab), resulting in a worsening prognosis 2 , 3 . Studies have shown that in MM, there is dysregulation of the immune compartment in the bone marrow, including changes in major cell populations such as natural killer (NK) cells, CD4 + and CD8 + T cells, and dendritic cells, and increases in immune suppressive cell populations, including regulatory T cells (T reg ), tumor-associated macrophages (TAMs), and myeloid-derived suppressor cells (MDSCs) 4 8 . It has been demonstrated that programmed cell death protein-1 (PD-1) expression is upregulated on T cells isolated from patients with MM, suggesting that this pathway is of importance in mediating the immunosuppressive state in this patient population 9 .…”
Section: Introductionmentioning
confidence: 99%